Dilute nitric or nitrous acid solution containing halide ions as effective media for pure gold dissolution. Issue 30 (14th August 2015) - Hojo, Masashi; Yamamoto, Masahiko; Okamura, Kei
<x xml:space="preserve">Abstract</x> Bromide salts are more effective than chloride salts in gaining the ability of dissolving gold in dilute aqueous nitric acid solution. At 60 °C, a piece of gold-wire (ca. 20 mg) is dissolved in 20 mL of as low as 0.10 mol L−1 HNO3 solution containing 1.0–5.0 mol L−1 NaBr and the dissolution rate constant, log(k/s−1), increases linearly with increasing NaBr concentration.